RHU 3D SEISMIC DATA REPROCESSING, OFFSHORE PENINSULAR MALAYSIA - Boon Hong, Philip Goh (2016)
It is essential in petroleum exploration to have high resolution subsurface images, both vertically and horizontally, in uncovering even further the geological and geophysical aspects of our subsurface. The discovery of oil in the upper Penyu Formation of the Rhu field back in 1991 proved the existence of a petroleum system and has steered more exploration, but soon abandoned in year 1995 because of its sub commercial value (Anuar and Madon, 1999). In 2011, another discovery was made at Rhu but at a different play. Past exploration had declared Rhu to have a no potential to produce hydrocarbon commercially. The lack of success may have been from the poor imaging quality which led to inaccurate analysis and interpretation. This project focuses on reprocessing the available Rhu field seismic data acquired by WesternGeco in 2004 and initially reprocessed by CGGVeritas in 2009. The aim of reprocessing the current seismic data puts emphases on two objectives. First is to produce an even higher quality 3D dataset with full retention of relative amplitudes and significantly reduce seismic and structural uncertainty. Secondly, to facilitate further prospect delineation through enhanced data resolution, fault definitions and events continuity, particularly in Syn-rift section and Basement cover contacts and in turn, better understand the geology of the subsurface especially in regard to the distribution of the fluvial/channel sands. By adding recent, state-of-the-art processing techniques like deghosting, closely spaced (or high density) velocity analysis, shallow water demultiple (SWD), coherency 3D and curvelet domain bandwidth extenstion (CDBandEx) the final results would have much better overall reflection detail and frequency bandwidth, especially at the target area.